STRATEGI EKSPOR PT LEGEND TREN INTERNASIONAL DALAM MEMBAWA MINUMAN LOKAL KE PASAR INTERNASIONAL - Cahya Lingga Wulandary; Resa Rasyidah (Halu Oleo University, 2024)
Currently, MSMEs not only market their products to the domestic market but also to the international market. One is PT Legend Tren Internasional, which brings traditional local drinks to the international market. Legen drink or siwalan sap water is a product from Tuban City that PT Legend Tren Internasional processes as a product that is low in sugar and suitable for people with diabetes. The brand image emphasized in this product is typical of the Indonesian archipelago, which is global. The research discusses the company's export strategy, which uses the concepts of product adaptation and innovation strategies, product quality standardization strategies, and export promotion strategies. This research is qualitative research with primary data sources through interviews and secondary data to find out the strategies of Legend Tren International in introducing products and exporting them to various countries. This MSME does not have competitors, so it is an opportunity to market its products internationally. They have already exported products to Hong Kong, Singapore, and Nigeria.